Magnesium Inhibits Platelet Activity - an Infusion Study in Healthy Volunteers - Ravn, Hanne Berg; Vissinger, Henrik; Kristensen, Steen Dalby; Wennmalm, Aake; Thygesen, Kristian; Husted, Steen Elkjcer (Thrombosis and Haemostasis, 1996)
Magnesium (Mg) has shown the ability to inhibit arterial thrombus formation in some experimental animal studies. This effect may be due to an inhibition of platelet reactivity as in vitro studies have demonstrated that Mg inhibits platelet aggregation. In order to evaluate the in vivo effect of Mg in humans measurements of platelet activity, fibrinolytic activity, as well as measurements of prostacyclin (PGI2), and nitric oxide (NO) release were performed after infusion of magnesium sulphate (MgSO4) in healthy volunteers. In a placebo controlled, cross-over study in 14 healthy male subjects, 8 mmol MgSO4 was given as an intravenous bolus over 15 min followed by 3 mmol MgSO4/h.The mean S-Mg concentration increased from 0.85 to 1.50 mM during the Mg infusion period. A transient decrease in blood pressure was observed during the initial bolus infusion of Mg. Haemodynamic parameters were otherwise stable. The bleeding time increased by 48% during the Mg infusion (p <0.005), and in accordance with this, ex vivo platelet aggregation in platelet rich plasma was significantly inhibited, both following collagen (p = 0.02) and ADP (p = 0.04) stimulation. There were no significant changes in plasma beta-thromboglobulin concentration or the excretion of 2,3-dinor-thromboxane B2 in the urine. Neither tissue plasminogen activator (t-PA)activity, tissue plasminogen activator (t-PA)antigen nor plasminogen activator inhibitor (PAI)antigen changed during the Mg infusion period. There was no sign of increased release of PGI2 from the vessel wall as judged by urinary concentration of 2,3-dinor-6-keto-prostaglandin F1α. Nor was there any sustained increase in the release of NO, measured as nitrate concentration in urine. However, a transient increase in NO release was observed during one sample period.In conclusion a reduced platelet activity and increased bleeding time, was found during Mg infusion in healthy volunteers. Fibrinolytic activity showed no changes. An anti-platelet effect may in part be responsible for the beneficial effect of Mg, described in patients with acute myocardial infarction (MI) and preeclampsia.